COMMUNICATION MODEL OF THE HEAD OF HIMIKOM IN MANAGING THE ORGANISATION IN THE ENVIRONMENT OF DHARMAWANGSA UNIVERSITY - Nirwana, Nirwana; Aulia, Nabila; Hasugian, Buyung Solihin (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
The purpose of this study is to analyze the communication model of the Himikom organization leadership in embracing the thoughts of each member, the objective conditions of motivation to members, and what are the supporting and inhibiting factors in the leadership communication model in realizing the vision and mission of the organization. This type of research is naturalistic with a qualitative approach. The subjects of this research are the Chairperson of Himikom and its members at Dharmawangsa University Campus, Faculty of Social and Political Sciences, Communication Science Study Program. The object of this research is the communication model of the Chairperson and Members in realizing the vision and mission of the Communication Science Student Association. The results of the analysis of this study indicate that, the communication model of the Chairperson of the Communication Science Student Association Organization in running the wheels of the organization, namely: Linear communication model is a unidirectional communication model, namely communication only from one party, while the other party is only the recipient. This model is essentially a unidirectional communication model, based on the assumption that the organization's leader has a direct, immediate, and very decisive influence on the course of the organization. The communication model has encountered several obstacles such as: lack of member response to policies made by the leadership, lack of responsibility of each member in every organizational activity, lack of member interest to always be active in the organization, and will hamper all work programs that have been designed because they are closed to suggestions and criticism from members.